Tracking the Evolution of Polymer Interface Films during the Process of Thermal Annealing at the Domain and Single Molecular Levels using Scanning Tunneling Microscopy - Duan, Xiao-Ling (Langmuir : the ACS journal of surfaces and colloids, 2016)
Structural evolution of polymer (NTZ12) interface films during the process of annealing is revealed at the domain and single molecular levels using the statistical data measured from scanning tunneling microscopy images and through theoretical calculations. First, common features of the interface films are examined. Then, mean values of surface-occupied ratio, size and density of the domain are used to reveal the intrinsic derivation of the respective stages. Formation of new domains is triggered at 70 °C, but domain ripening is not activated. At 110 °C, the speed of formation of new domains is almost balanced by the consumption due to the ripening process. However, formation of new domains is reduced heavily at 150 °C but restarted at 190 °C. At the single molecular level, the ratio of the average length of linear to curved backbones is increased during annealing, whereas the ratios of the total length and the total number of linear to curved skeletons reaches a peak value at 150 °C. The two major conformations of curved backbones for all samples are 120° and 180° bending, but the ripening at 150 °C reduces 180° folding dramatically. Molecular dynamic simulations disclose the fast relaxing process of curved skeletons at high temperature